Studi Farmakovigilans Obat Herbal Di Kota Banjarmasin Dengan Metode Naranjo - Darini Kurniawati; Iwan Yuwindry (LPPM Universitas Sari Mulia, 2021)
Background: Basic Health Research of the Republic of Indonesia in 2018 obtained data that 30.4% of Indonesian people consume traditional herbal medicine in homemade ingredients. The Indonesian government encourages the use of herbs because the raw materials for finished drugs are still obtained from abroad (Dani Pratama, 2020). The purpose of this study was to see the possibility of side effects on the use of herbal medicines for the people of Banjarmasin using the Naranjo method. This research method is descriptive observational with a cross sectional design with purposive sampling with inclusion and exclusion criteria set by researchers in the North Banjarmasin District. Data analysis using Naranjo. The results of the research from the dominant age characteristics data are aged 31-50 years as many as 13 (42%), the majority gender is 22 (71%), the majority of the work status is self-employed 19 (61 %), the majority of the education status is SMA 15 (48 %), majority income status above two million 10 (32 %). The majority of people use herbal medicines 27 (87%), sources of information on herbal medicines from families 20 (65%), the majority of herbal medicines are from traditional medicine shops 11 (35%), the majority of herbal medicines are brewed 11 (35%). From the causality analysis using the Naranjo algorithm, it is known that the patients who used herbal medicines had 6 subjects in the possible category. Conclusion: The incidence of side effects of using herbal medicines in the Possible category. Keywords: herbal medicine, Naranjo, Possible.